Mobilized Peripheral Blood versus Cord Blood: Insight into the Distinct Role of Proinflammatory Cytokines on Survival, Clonogenic Ability, and Migration of CD34+ Cells - Dorian Forte; Daria Sollazzo; Martina Barone; Marisole Allegri; Angela di Martella Orsi; Marco Romano; Barbara Sinigaglia; Giuseppe Auteri; Nicola Vianelli; Michele Cavo; Francesca Palandri; Lucia Catani (Hindawi Limited, 2018)
Inflammation may play a role in cancer. However, the contribution of cytokine-mediated crosstalk between normal hemopoietic stem/progenitor cells (HSPCs) and their (inflammatory) microenvironment is largely elusive. Here we compared survival, phenotype, and function of neonatal (umbilical cord blood (CB)) and adult (normal G-CSF-mobilized peripheral blood (mPB)) CD34+ cells after in vitro exposure to combined crucial inflammatory factors such as interleukin- (IL-) 1β, IL-6, tumor necrosis factor- (TNF-) α, or tissue inhibitor of metalloproteinases-1 (TIMP-1). To mimic bone marrow (BM) niche, coculture experiments with normal BM stromal cells (BMSCs) were also performed. We found that combined inflammatory cytokines increased only the in vitro survival of CB-derived CD34+ cells by reducing apoptosis. Conversely, selected combinations of inflammatory cytokines (IL-1β + TNF-α, IL-6 + TNF-α, and IL-1β + TNF-α + TIMP-1) mainly enhanced the in vitro CXCR4-driven migration of mPB-derived CD34+ cells. TNF-α, alone or in combination, upregulated CD44 and CD13 expression in both sources. Finally, BMSCs alone increased survival/migration of CB- and mPB-derived CD34+ cells at the same extent of the combined inflammatory cytokines; importantly, their copresence did not show additive/synergistic effect. Taken together, these data indicate that combined proinflammatory stimuli promote distinct in vitro functional activation of neonatal or adult normal HSPCs.